Serum testosterone profile in breeding rams - SUTHAR, B N; SHARMA, V K; DUGWEKAR, Y G; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Serum testosterone profile of Patanwadi and half bred Merino rams was studied to ascertain the effect ofbreed. season and semen collection stimulus. Patanwadi rams had a significantly higher concentration of hormone(6 .1 :! ± 0.39 ngtml.) with a concomitant rise during the breeding season (6.89 ± 0.61 ng/ml.) in comparison to halfbred Merinos (4.58 ± 0.37 ngtml.). In both the breeds. testosterone increased significantly just prior to semencollection. 7.38 ± 0.53 and 6.00 ± 0.43 ng/ml.; and thereafter decreased to lowest following 60 minutes later toejaculation. 4.89 ± 0.48 and 3.12 ± 0.49 ng/ml. in Patanwadi and cross bred rams, respectively. It was concluded fromthe results that blood serum testosterone profile was influenced by the breed and semen collection stimulus inboth breeds while. seasonal variations were restricted to only Patanwadi rams.
Keywords: Testosterone; season; breed; collection stimulus